Penerapan Hidroponik Sistem Nutrient Film Technique (NFT) Di Politeknik Hasnur - Linda Rahmawati; Herry Iswahyudi; Baimy Alexander (Program Studi Budidaya Tanaman Perkebunan, Politeknik Hasnur, 2020)
The development of aquaculture with a hydroponic system is now more and more chosen by the community because of the increasingly limited land, but also comparable to the increasing demand for water. Hydroponics with the Nutrient Film Technique (NFT) system can be used as a solution to the water needs needed in the cultivation of hydroponics plants. This study aims to design the hydroponic installation of the NFT system and grow plants in the NFT system. The study was conducted with the stages of making the hut, making the installation, seeding, making nutritional solutions and transferring seed to the installation. The research will be conducted for five months. Descriptive research with qualitative data obtained is the way of making the NFT system, plant growth speed and the amount of water needed. Making the installation begin with the construction of the hut and shade then arranges the installation. For lettuce, the harvest time is 38 days dan tomatoes 50 days after the plants are moved to the plant. The need for water in the NFT hydroponic system is 190 liters.